HUBUNGAN ANTARA BODY IMAGE SATISFACTION DAN SELF-ESTEEM PADA PEREMPUAN DEWASA MUDA YANG BERDIET DI JAKARTA - Vera Ignatia Prawono (Psibernetika, 2013)
The purpose of this study is to check if there is a significant correlation between body image satisfaction and self-esteem among early adult women while dieting in Jakarta. Dieting is the most way to dealing with body dissatisfaction in women. It is assumed that dieting women might have high body image satisfaction and also high in self-esteem. If the dieting mowen have low body image satisfaction, they might also have low self-esteem. Participants of this study are 100 women between 20-30 years old, having popular diet (unhealthy diet) for 3 months or more, living in Jakarta, and having an average or normal BMI (Body Mass Index). This study uses purposive sampling for the sampling technique. Participants were given 2 questionnaires, Multidimensional Body-Self Related Questionnaire by Cash dan Self-Esteem Scale by Rosenberg. The result shows a significant correlation between body image satisfaction and self-esteem among early adult women while dieting in Jakarta. Further discussion explains about other score combinations among participants. High body image satisfaction doesn’t always correlated with high self-esteem, vice versa. This study also gives a general capture about the reasons for dieting among respondents not only because of their own desires and body image satisfaction is not the only one factor that affects someone’s self-esteem. Keyword: body image satisfaction, self esteem, woman